Vinyl in the Asian sixties : album art, transnational migration and popular culture in mid-twentieth century Singapore - Boey, Brenda Qian Hui (2017)
This essay examines locally produced vinyl record covers from 1963 to 1970 and argues that they recover an organic modernity that was coming into being before commercial arts were institutionalized by the post-independence government in 1968. As time capsules, album art document modern Singapore fashions and socio-visual transformations, particularly how Chinese letters respond to Western typography. To borrow an advertising term, such album art is “copy-driven” where the design follows a standard template but innovation comes through in song selections and typography. Design-driven album art that illustrates psychedelic and flower power trends in music demonstrates local artists’ interpretations and consciousness of global socio-political trends. The troubled and inconsistent portrayal of multiracialism in “copy-driven” album art demonstrates that shifting creative decisions made during the production process was done so by responding to domestic politics. As commercial products created to please domestic audience and optimize market consumption, album art must be contextualised as a form of transnational communication that navigates decolonisation, political independence, national identity and personal expression during the Asian Sixties. A prolegomenon to music packaging, which is one of Singapore’s many design histories, this essay ends by reflecting on its limitations and future possibilities.